Identification and assessment of alleles in the promoter of the Cyc‐B gene that modulate levels of β‐carotene in ripe tomato fruit. Issue 1 (18th February 2021) - Orchard, Caleb J.; Cooperstone, Jessica L.; Gas‐Pascual, Elisabet; Andrade, Marcela C.; Abud, Gabriel; Schwartz, Steven J.; Francis, David M.
Abstract: Novel diversity may be mined from databases and de novo sequencing, but functional characterization remains a limiting step to identifying new alleles. Classical breeding approaches augmented by marker‐assisted selection offer a means to rapidly assess the function of new variation in coding or regulatory regions to modulate traits. We used the Cyc‐B gene ( B ) of tomato ( Solanum lycopersicum L.) for a proof of concept because of its role in the production of β‐carotene, a provitamin A carotenoid with importance to human nutrition. We measured carotenoid content in vintage and contemporary varieties and the profiles had a range of β‐carotene from 0.2 to 4.06 mg 100 g −1 fresh weight. We characterized variation in B from 84 sequences recovered from public databases and from an additional 29 high β‐carotene tomato, S. galapagense S. C. Darwin & Peralta, and S. cheesmaniae (L. Riley) Fosberg accessions. Thirteen unique haplotypes across 1600 bp of sequence 5′ to the first ATG were identified with 11 occurring in high β‐carotene accessions we sequenced, and additional haplotypes were identified in public data. Phylogenetic analysis suggested that the alleles in high β‐carotene varieties were derived from wild species. Association analysis suggested two single nucleotide polymorphisms (SNPs) as the most likely causes of high β‐carotene, presumably through their influence on transcription of B that is elevated in ripening fruit. A marker‐assisted backcross breeding scheme leveraging SNPs for background genome selection was used to rapidly develop germplasm resources containing different alleles of B in a uniform genetic background. Evaluation demonstrated that distinct promoter haplotypes function as different alleles that can be used to modulate the levels of β‐carotene in tomato. Core Ideas: The region 5′ to Cyc‐B is diverse with distinct haplotypes among high β‐carotene tomato. Cyc‐B haplotypes found in vintage and contemporary varieties are from wild species. SNPs shared between the green‐fruited clade and the Galápagos islands are likely functional. Marker‐assisted backcrossing was used to rapidly introgress natural variation for assessment. Fine‐tuning of β‐carotene content in tomato is possible using natural allelic variation.